Hand muscle strength in Parkinson's disease: A Sarcopenic epiphenomenon or a meaningful biomarker? - Saarinen, Emmi K.; Kuusimäki, Tomi; Niemi, Kalle; Noponen, Tommi; Jaakkola, Elina; Myller, Elina; Eklund, Mikael; Nuuttila, Simo; Ihalainen, Toni; Murtomäki, Kirsi; Mertsalmi, Tuomas; Levo, Reeta; et al. (ELSEVIER SCI LTD, 2026)
Introduction: Sarcopenia, the age-related loss of muscle mass and function, has been reported in Parkinson's disease (PD). While grip strength is a key marker of sarcopenia and has been linked to PD risk and progression, its relationship with underlying neurodegenerative processes remains unclear. This study examines whether grip strength is impaired in PD and reflects disease severity or dopaminergic function.
Methods: Grip strength was assessed in 147 PD patients and 35 healthy controls, alongside motor symptoms and striatal dopamine transporter (DAT) binding using [123I]FP-CIT single photon emission computed tomography. Longitudinal follow-up included 84 PD patients with clinical reassessment (median 4.1 years) and 40 patients with both clinical and DAT imaging re-evaluations (median 6.2 years). Associations between grip strength, motor symptom severity and dopaminergic function were analyzed.
Results: At baseline, mean grip strength did not differ between PD patients and healthy controls, and it did not correlate with striatal DAT binding (p > 0.37). While striatal DAT binding declined in PD (4.2 % annually, p < 0.001) and was associated with worsening motor function (p = 0.004), grip strength was not independently associated with DAT binding decline (p > 0.62). However, grip strength declined alongside worsening motor symptoms (p = 0.029).
Conclusion: Upper limb muscle strength remains largely preserved in mild to moderate PD and does not reliably reflect dopaminergic function or disease progression. Although sarcopenia has been reported in PD, grip strength declines in parallel with motor symptom progression and DAT loss rather than directly reflecting the disease process, suggesting it is an epiphenomenon rather than an independent pathophysiological feature.